2020
DOI: 10.1002/ijfe.2131
|View full text |Cite
|
Sign up to set email alerts
|

Does trade openness andFDIreduce inequality? Evidence from South Asia

Abstract: This study seeks to examine whether trade openness and inward FDI may affect income distribution in an unbalanced panel of five South Asian countries over the period of 1990-2016. The analysis of the model involves the examination of likely non-linear effect of both trade and FDI on income distribution. Therefore, dynamic panel system-generalized method of moments (SYS-GMM) estimator has been applied to mitigate the problem of nonlinearity and possible endogeneity. In the second stage, the model is extended to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Although existing studies on the relationship between trade opening and income disparity found that trade opening reduces labor income share, thereby widening income disparity (Jayadev, 2007 ; Asteriou et al, 2014 ), these empirical analyses mainly focused on trade opening among developed economies, while this paper focuses on a developing country. Contrary to the conclusions of these studies, many studies suggested that when countries engage in trade opening, the production factors that are relatively abundant gain, especially in developing countries can gain a larger share of labor income through trade opening, which in turn leads to a decrease in income inequality (Jaumotte et al, 2013 ; Roser and Cuaresma, 2016 ; Khan et al, 2020 ; Dorn et al, 2022 ). These previous studies further provide empirical support for the rationality of the research hypothesis in this paper.…”
Section: Discussionmentioning
confidence: 88%
“…Although existing studies on the relationship between trade opening and income disparity found that trade opening reduces labor income share, thereby widening income disparity (Jayadev, 2007 ; Asteriou et al, 2014 ), these empirical analyses mainly focused on trade opening among developed economies, while this paper focuses on a developing country. Contrary to the conclusions of these studies, many studies suggested that when countries engage in trade opening, the production factors that are relatively abundant gain, especially in developing countries can gain a larger share of labor income through trade opening, which in turn leads to a decrease in income inequality (Jaumotte et al, 2013 ; Roser and Cuaresma, 2016 ; Khan et al, 2020 ; Dorn et al, 2022 ). These previous studies further provide empirical support for the rationality of the research hypothesis in this paper.…”
Section: Discussionmentioning
confidence: 88%
“…Khan (2020) examines whether trade openness and inward FDI may affect income distribution in an unbalanced panel of five South Asian countries over the period of 1990-2016. The results reveal that trade and FDI have significant effects on income inequality, however, inverted Ushaped curve holds for trade as purposed by the trade theory [13]. Basnet (2020) examines the long-run impact of terms of trade (TOT) on economic growth in the context of eight South and Southeast Asian emerging economies.…”
Section: Trade and Economic Growthmentioning
confidence: 99%
“…However, the findings issued by these are inconclusive. While some scholars found that trade openness could contribute to exacerbating income inequality (Khan et al, 2020;Xu et al, 2021), others show that trade openness could contribute to lessening income inequality (Canh et al, 2020;Le et al, 2020). Trade openness has been proxied by the sum of imports and exports divided by GDP.…”
Section: • Trade Openness (Top)mentioning
confidence: 99%